Analisa Tata Ruang Kantor dan Pengaruhnya terhadap Kinerja Pegawai - Asra Novita Risha; Asep Erik Nugraha (Fakultas Teknik, 2022)
Human Resource Management is an important key for the company. The quality of human resources can be seen from the performance of each individual. The performance can be caused by several factors. The office is an environment that is a place for an organization to work in achieving its goals. Poor office space arrangement can certainly hinder the flow of activity in completing tasks while in the office. This study aims to examine the influence of office layout on the performance of employees of the Community and Village Empowerment Service of Karawang Regency with a sample of 32 people. Researchers use quantitative research. Meanwhile, for data collection using observation techniques through questionnaires. Simple linear regression was used as the data analysis method. Data processing is assisted by SPSS and Microsoft Excel. The research resulted in an acceptable hypothesis, where the office layout variable positively affects employee performance. These results can be used as input and descriptions of leaders in improving employee performance through office layouts that can be worn to support performance improvements.